Challenging the Literacy of ‘Literacy and Numeracy’: The Potential for Film and Moving Image Media in the Irish Educational Landscape - McGraw Lewis, Thomas (Irish Journal of Arts Management and Cultural Policy, 2013)
This paper argues that despite a nationally sanctioned plan of action that sees media literacy as little more than the capacity to send an email, recent changes to curricular policy and intent at subject-specific and cycle-wide levels are making spaces for the possibility of wider film usage within Irish education. In its overview of the contemporary pedagogical landscape, the assertion is made that many benefits would come from such inclusion. The analysis asserts that the unique capacities of dialogic, multimodal engagement can incentivise learning and strengthen direct curricular support as well as wider outcomes-based objectives oriented within, and beyond, the four walls of the Irish classroom. It is argued that the time to engage in such thinking is now. Coupled with a host of initiatives and arguments from educational, cultural and media industry stakeholders, the exploration of such possibilities, new models of filmic engagement, and a greater emphasis on media literacy skillsets, is necessary to equip Irish students for both scholastic endeavour and wider civic participation.